2007
DOI: 10.1128/aem.01251-07
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Vaginal Bacterial Communities in Women Developing Bacterial Vaginosis, Candidiasis, or No Infection, Analyzed by PCR-Denaturing Gradient Gel Electrophoresis and Real-Time PCR

Abstract: The microbial flora of the vagina plays a major role in preventing genital infections, including bacterial vaginosis (BV) and candidiasis (CA). An integrated approach based on PCR-denaturing gradient gel electrophoresis (PCR-DGGE) and real-time PCR was used to study the structure and dynamics of bacterial communities in vaginal fluids of healthy women and patients developing BV and CA. Universal eubacterial primers and Lactobacillus genus-specific primers, both targeted at 16S rRNA genes, were used in DGGE and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
76
0
5

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(85 citation statements)
references
References 43 publications
4
76
0
5
Order By: Relevance
“…Since the first microbiological study of the human vagina, lactobacilli have been considered the dominant members of the microbiota of this organ (Doderlein, 1982), a finding that has been further confirmed by several recent metagenomic studies (Biagi et al, 2009;Fettweis et al, 2012;Martín et al, 2014;Pavlova et al, 2002;Song et al, 1999;Verhelst et al, 2004;Vitali et al, 2007;Wilks et al, 2004;Zhou et al, 2004). In total, around 20 different species of lactobacilli have been consistently isolated from the vagina, although only one or two species predominate at a time in a given individual.…”
Section: Introductionmentioning
confidence: 61%
See 1 more Smart Citation
“…Since the first microbiological study of the human vagina, lactobacilli have been considered the dominant members of the microbiota of this organ (Doderlein, 1982), a finding that has been further confirmed by several recent metagenomic studies (Biagi et al, 2009;Fettweis et al, 2012;Martín et al, 2014;Pavlova et al, 2002;Song et al, 1999;Verhelst et al, 2004;Vitali et al, 2007;Wilks et al, 2004;Zhou et al, 2004). In total, around 20 different species of lactobacilli have been consistently isolated from the vagina, although only one or two species predominate at a time in a given individual.…”
Section: Introductionmentioning
confidence: 61%
“…In total, around 20 different species of lactobacilli have been consistently isolated from the vagina, although only one or two species predominate at a time in a given individual. Dominant strains vary as a function of race and lifestyle, but strains of Lactobacillus crispatus, Lactobacillus iners, Lactobacillus jensenii and Lactobacillus gasseri are the most frequent (Biagi et al, 2009;Pavlova et al, 2002;Song et al, 1999;Verhelst et al, 2004;Vitali et al, 2007;Wilks et al, 2004;Zhou et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Their sample size was very small though. Studies have shown that alteration of or abnormal vaginal bacterial flora predispose to RVVC only in the presence of antibiotic use [58,59]. It is worth noting thought that the majority of women who receive antibiotics do not develop genital candidiasis and majority of women with genital candidiasis have not used antibiotics in the immediate past.…”
Section: Antibiotic Therapymentioning
confidence: 99%
“…However, it is still unclear whether the primary event for BV onset is the loss of Lactobacillus species or the acquisition of complex microbial communities found in this syndrome, or both [5,9]. In this context, vaginal microbial structure characterization in BV and non-BV women is important to understand the complex etiology of this disease, especially considering the non-Gardnerella vaginalis species [1,12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Microorganisms inhabiting the vaginal environment are constantly submitted to selective pressures, like immune response and pH, which contribute to ecosystem balance and modulate its distribution on resident microbiota [1]. Therefore, the health status of female genital tract is dependent on the vaginal bacterial community [2].…”
Section: Introductionmentioning
confidence: 99%